Specificity and Abstraction of Examples: Opposite Effects on Fixation for Creative Ideation. (16th May 2018) - Ezzat, Hicham; Agogué, Marine; Le Masson, Pascal; Weil, Benoit; Cassotti, Mathieu
Abstract: Fixation is one of the major obstacles that individuals face in creative idea generation contexts. Several studies have shown that individuals unintentionally tend to fixate to the examples they are shown in a creative ideation task, even when instructed to avoid them. Most of these studies used examples formulated with high level of specificity. However, no study has examined individuals' creative performance under an instruction to diverge from given examples, when these examples are formulated with a high level of abstraction. In the present study, we show that (a) instructing participants to avoid using common examples when formulated with a high level of specificity increases fixation; whereas (b) instructing participants to avoid such examples while using a more abstract level for stating these common examples—such as a categorization of these examples—mitigates fixation and doubles the number of creative ideas generated. These findings give new insights on the key role of categorization in creative ideation contexts.